(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Today, the increase in demand for cotton fibre requires the improvement of cotton ginning equipment and the analysis of their technological processes. The main first stage of the cotton gin is the transfer of the harvested cotton to the production workshop. In this article, the horizontal feeder to the cotton pneumatic transport pipeline used in cotton gins is analyzed and recommendations are given.